High sensitivity cardiac troponin T in patients not having an acute coronary syndrome: results from the TRAPID-AMI study. (17th November 2017) - Nowak, Richard; Mueller, Christian; Giannitsis, Evangelos; Christ, Michael; Ordonez-Llanos, Jordi; DeFilippi, Christopher; McCord, James; Body, Richard; Panteghini, Mauro; Jernberg, Tomas; Plebani, Mario; Verschuren, Franck; et al.
Abstract: Purpose: To describe the baseline, 1 hr and delta high sensitivity cardiac troponin (hs-cTnT) values in patients with suspected acute myocardial infarction (AMI) but without a final acute coronary syndrome (ACS) diagnosis. Materials and methods: hs-cTnT assay forRAPID rule out of acute myocardial infarction (TRAPID-AMI) was a prospective diagnostic trial that enrolled emergency department (ED) patients with suspected AMI. Final patient diagnoses were adjudicated by a clinical events committee and subjects placed in different clinical groups: AMI, unstable angina, non-ACS cardiac, non-cardiac and unknown origin. The baseline, 1 hr and delta hs-cTnT values were analysed in the 902 non-ACS patients. Results: Amongst the 1282 studied the patient groups were 213 (17%) AMI, 167 (13%) unstable angina, 113 (9%) non-ACS cardiac, 288 (22%) non-cardiac and 501 (39%) unknown origin. The hs-cTnT values in the non-cardiac and unknown origin groups were combined. The median hs-cTnT values (ng/L) were higher ( p  < 0.001) in the non-ACS cardiac compared to the non-cardiac/unknown origin group at baseline (11.8,  <5) and 1 hr (12.3,  <5). Their negative predictive values were 0.955 (baseline) and 0.954 (1 hr) for predicting non-ACS cardiac versus non-cardiac/unknown origin diagnoses. Conclusions: Hs-cTnT may help predict whether non-ACS ED patients have a final non-ACS cardiac or non-cardiac/unknown origin diagnoses.